Method for coating sodium ion layered oxide positive electrode material by wet process
The wet coating method is used to form a uniform nano-scale oxide coating layer on the surface of the positive electrode material of the sodium ion battery, which solves the air stability and cycle life of the positive electrode material, and achieves a more stable interface and a simplified process.
Patent Information
- Application Number
- CN202411854379.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The existing sodium ion battery positive electrode materials have poor air stability and short cycle life. The residue of sodium salt during the preparation process leads to an increase in surface residual alkali, which affects processing performance and safety.
Using the wet coating method, a uniform nano-scale oxide coating layer is formed on the surface of the layered oxide positive electrode material of sodium ion battery, and the hydrolysis of the metal organic salt in the alcohol solvent is controlled by ammonia water to form oxide coating layers such as Al2O3, TiO2, ZrO2, etc.
It effectively improves the air stability and circulation performance of the material, reduces the pH value, avoids direct contact between the positive electrode material and the electrolyte, ensures the stability of the interface, and simplifies the control of process parameters.
Smart Images

Figure HDA0005191417500000011 
Figure HDA0005191417500000012 
Figure HDA0005191417500000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and particularly relates to a method for wet coating a sodium ion layered oxide positive electrode material. Background Art
[0002] With the rapid development of global new energy, the popularity of electric vehicles and the increasing application of electrochemical energy storage, however, in the electrochemical energy storage system, battery technology is the most core link and also the link with the highest barriers in the current industrial chain. The current mainstream electrochemical energy storage technology is lithium-ion batteries. However, the low content of lithium resources in the earth's crust, high cost, safety and service life have increasingly failed to meet people's requirements for electrochemical energy storage. Therefore, sodium-ion batteries have emerged as a new type of secondary chemical power source. Sodium-ion batteries have entered people's field of vision due to their rich crustal content, low price, high energy conversion efficiency, long cycle life, safety and other advantages, and are expected to complement lithium-ion batteries in electric vehicles and electrochemical energy storage. At present, sodium-ion batteries have certain technical conditions and industrialization conditions.
[0003] Among all kinds of positive electrode materials for sodium-ion batteries, O3-type layered oxide positive electrode materials have attracted widespread attention due to their unique advantages. They have high original sodium content, high theoretical specific capacity, simple preparation process and low price. However, there are also a series of disadvantages, such as poor air stability and poor cycle life. In particular, in the process of preparing positive electrode materials for sodium-ion batteries, excessive sodium salts are often added to make up for the loss of sodium in the process, which will result in residual sodium salts after sintering. These residual sodium salts exist in the positive electrode material in the form of sodium carbonate or sodium hydroxide, that is, residual alkali. At the same time, the precipitation of sodium ions is also very easy to react with water molecules or carbon dioxide in the air, which will lead to an increase in residual alkali on the surface of the positive electrode material. Therefore, the layered positive electrode material of the sodium-ion battery absorbs water and moisture during the processing process, which will cause the slurry to appear jelly-like, increase viscosity, and deteriorate processing performance, thus causing safety problems.
[0004] Therefore, how to improve the air stability of O3-phase layered oxides, reduce the pH value, and then improve the battery's cycle performance and rate performance has become one of the key issues in sodium-ion battery related technologies. Currently, the commonly used modification methods include surface coating, component regulation, and structural design of layered positive electrode materials. Among them, surface coating is a relatively effective method. It can coat a physical protective layer on the surface of the material, which can inhibit the volume change during charging and discharging. At the same time, it can also reduce the direct contact between the positive electrode material and the electrolyte and reduce interfacial side reactions. At present, there are roughly four types of coating materials for sodium-ion battery positive electrode materials: metal oxides, non-metallic element coatings, sodium / lithium fast ion conductors, organic matter / conductive polymers, etc. There are roughly three types of coating methods: deposition technology, sol-gel / coprecipitation, solid phase method, etc. Chinese patent application CN117525338A discloses a coated modified sodium battery positive electrode material to reduce the generation of residual alkali on the surface. The patent uses a wide range of coating materials such as metal oxides, metal organic salts and metal phosphates, but the method used is dry mixing, including mortar grinding, ball mill, high-speed mixer or granulator. The coating layer manufactured by dry mixing is usually uneven, and the coating material usually presents an island-like coating on the surface of the coated material. In addition, due to the particle size of the coating material, it is difficult to make the coating layer very thin. This non-uniform coating has limited protective effect on the sodium ion positive electrode material. The principle of wet coating is essentially different from that of dry coating. Usually, the precursor of the coating material is dissolved in a solution first, and then certain conditions are controlled so that the coated material is hydrolyzed or precipitated from the precursor solution. When precipitating, nucleation is usually formed on the surface of the coated material, so a uniform coating layer is formed to completely cover the coated material. By controlling the reaction conditions, it is easy to obtain a coating layer with a nanometer thickness, which not only protects the surface of the positive electrode material from side reactions, but also does not affect ion transmission due to the thickness. For example, Chinese patent application CN114122349A proposes a method for preparing an oxide-coated dual-element co-doped high-nickel ternary positive electrode material. In the embodiment, aluminum isopropoxide, tetraethyl titanate and ferric citrate are dispersed in ethanol to form a solution, and then deionized water is added to induce hydrolysis. After heat treatment under an inert atmosphere, aluminum oxide, titanium oxide and iron oxide coating layers are obtained respectively. Then this method is not effective in the coating of sodium ion layered positive electrode materials. Sodium-ion positive electrode materials are more alkaline than high-nickel ternary materials and react more easily with water. The hydrolysis reaction initiated by the addition of water is difficult to control. Summary of the invention
[0005] Purpose of the invention: In order to solve the defects of the prior art, the present invention provides a method for wet coating of sodium ion layered oxide positive electrode materials. The present invention adopts ammonia water to control the hydrolysis of metal organic salts in alcohol solvents to perform wet coating, forming a uniform nano-scale coating layer on the surface of the sodium ion battery layered oxide positive electrode material, and then converting it into an oxide coating layer through heat treatment, effectively controlling the reaction.
[0006] Technical solution: In order to achieve the above-mentioned invention object, the present invention adopts the following technical solution:
[0007] A method for wet coating a sodium ion layered oxide positive electrode material comprises the following steps:
[0008] S1. The layered oxide cathode material of the sodium ion battery is dispersed in a dispersant, and then a buffer solution containing a metal organic salt is added under heating and stirring to obtain a mixed solution;
[0009] S2. Add a certain amount of aqueous ammonia dropwise to the mixed solution, continue stirring, and perform hydrolysis and coating;
[0010] S3. After coating, filter, wash, dry, grind and calcine to obtain the product.
[0011] As a specific implementation scheme, in step S1, the sodium ion battery layered oxide positive electrode material is selected from NaNi x Fe y Mn 1-x-y O2, wherein 0.2≤x≤0.5; 0.1≤y≤0.4; the dispersant is selected from anhydrous ethanol.
[0012] As a specific implementation, in step S1, the metal organic salt is selected from aluminum isopropoxide, zirconium butoxide or tetrabutyl titanate; and the buffer solution is prepared by dissolving the metal organic salt in anhydrous ethanol to form a buffer solution.
[0013] As a specific implementation scheme, in step S1, the mass ratio of the sodium ion battery layered oxide positive electrode material to the metal organic salt is 1: (0.03-0.4); in the buffer solution, the concentration range of the metal organic salt solution is 1 mmol L -1 ~5mmol L -1 .
[0014] As a specific implementation scheme, in step S2, the pH range of the ammonia water is 10-12, and the amount of ammonia water added is 1%-5% of the volume of the mixed solution.
[0015] As a specific implementation, in step S2, the time for hydrolysis and coating is 20 to 30 minutes.
[0016] As a specific implementation scheme, in step S3, the drying time is 5 to 7 hours; the calcination temperature is 600°C to 700°C.
[0017] The present invention also provides a sodium ion layered oxide positive electrode material, which is prepared by the above method.
[0018] Finally, the present invention provides the application of the sodium ion layered oxide positive electrode material in the preparation of a sodium ion battery.
[0019] Beneficial effects: The present invention coats the surface of the layered oxide positive electrode material of the sodium ion battery with oxides such as Al2O3, TiO2, and ZrO2 by controlling the hydrolysis of metal organic salts in an alcohol solvent. This method can effectively reduce the pH value of the material and improve the air stability of the material. Compared with the prior art, the present invention has the following advantages:
[0020] (1) To a certain extent, it avoids direct contact between the positive electrode material and the electrolyte, ensuring the stability of the interface;
[0021] (2) The particle surface and surface coating are relatively uniform;
[0022] (3) The preparation process is simple, the process parameters are easy to control, and it is easy to expand the scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD pattern of the titanium oxide-coated layered positive electrode material prepared in Example 1.
[0024] Figure 2 This is the XRD pattern of the alumina-coated layered positive electrode material prepared in Example 2.
[0025] Figure 3 This is the XRD pattern of the zirconium oxide-coated layered positive electrode material prepared in Example 3.
[0026] Figure 4 This is a SEM image of the titanium oxide-coated layered positive electrode material prepared in Example 1, magnified 15,000 times.
[0027] Figure 5 This is a SEM image of the alumina-coated layered positive electrode material prepared in Example 2, magnified 15,000 times.
[0028] Figure 6 This is a SEM image of the zirconium oxide-coated layered positive electrode material prepared in Example 3, magnified 15,000 times.
[0029] Figure 7The discharge capacity curves of sodium ion batteries assembled by using ammonia to hydrolyze tetrabutyl titanate to prepare TiO2@NFM (Example 1) and using the same volume of deionized water to hydrolyze tetrabutyl titanate to prepare TiO2@NFM positive electrode materials are compared under 25°C, 1C conditions for 50 cycles.
[0030] Figure 8 The discharge capacity curves of sodium ion batteries assembled with NFM coated in Examples 1, 2, and 3 and with uncoated NFM positive electrode materials at 25°C and 1C for 50 cycles. DETAILED DESCRIPTION
[0031] The technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] Example 1
[0033] ①Use a weighing balance to weigh 5 g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Pure O2 powder was dissolved in 100 ml ethanol in a 300 ml beaker and ultrasonically shaken for 10 min to make it evenly dispersed;
[0034] ② Use a weighing balance to weigh 0.388g of tetrabutyl titanate into a 150ml beaker, add 60ml of ethanol to make a buffer solution, place it on a magnetic stirring device, add a stirrer of appropriate size and stir for 20 minutes;
[0035] ③Ultrasonic vibration of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 suspension was placed in a magnetic stirring device and heated to 50 °C in a water bath and stirred for 5 min;
[0036] ④Adjust stirring NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The speed of the O2 suspension device is such that it is stirred vigorously, and then the prepared buffer solution is poured into the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 suspension to obtain a mixed solution, to which ammonia water with a pH of 11 was added dropwise, the amount of ammonia water added was 3% of the volume of the mixed solution, to hydrolyze the tetrabutyl titanate in the solution, and the solution was fully mixed, and then the speed was lowered and stirred for 30 min;
[0037] ⑤ The coated TiO2@NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 suspension is poured into a suction filtration device for filtration and washed 2 to 3 times;
[0038] ⑥ The filtered TiO2@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 powder was placed in a vacuum oven for 6 h and then ground appropriately;
[0039] ⑦Grind the TiO2@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was placed in an alumina crucible and calcined, starting from 20°C and heating up to 600°C at a rate of 5°C / min, and kept at 600°C for 4 hours, then cooled to room temperature and taken out.
[0040] Example 2
[0041] ①Use a weighing balance to weigh 5 g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Pure O2 powder was dissolved in 100 ml ethanol in a 300 ml beaker and ultrasonically shaken for 10 min to make it evenly dispersed;
[0042] ② Use a weighing balance to weigh 0.204 g of aluminum isopropoxide into a 150 ml beaker, add 60 ml of ethanol to make a buffer solution, place it on a magnetic stirring device, add a stirrer of appropriate size and stir for 20 min;
[0043] ③Ultrasonic vibration of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 suspension was placed in a magnetic stirring device and heated to 50 °C in a water bath and stirred for 5 min;
[0044] ④Adjust the stirring NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The speed of the O2 suspension device is such that it is stirred vigorously, and then the prepared buffer solution is poured into the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 suspension to obtain a mixed solution, to which ammonia water with a pH of 11 is added dropwise, the amount of ammonia water added is 3% of the volume of the mixed solution, to hydrolyze the aluminum isopropoxide in the solution, and the solution is fully mixed, and then the speed is lowered and stirred for 30 min;
[0045] ⑤ The coated NaNi 1 / 3 Fe1 / 3 Mn 1 / 3 The O2 suspension is poured into a suction filtration device for filtration and washed 2 to 3 times;
[0046] ⑥ The filtered Al2O3@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 powder was placed in a vacuum oven for 6 h and then ground appropriately;
[0047] ⑦ Grind the Al2O3@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was placed in an alumina crucible and calcined, starting from 20°C and heating up to 600°C at a rate of 5°C / min, and kept at 600°C for 4 hours, then cooled to room temperature and taken out.
[0048] Example 3
[0049] ①Use a weighing balance to weigh 5 g NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Pure O2 powder was dissolved in 100 ml ethanol in a 300 ml beaker and ultrasonically shaken for 10 min to make it evenly dispersed;
[0050] ② Use a weighing balance to weigh 0.327g zirconium butoxide into a 150ml beaker, add 60ml ethanol to make a buffer solution, place it on a magnetic stirring device, add a suitable size stirrer and stir for 20 minutes;
[0051] ③Ultrasonic vibration of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The O2 suspension was placed in a magnetic stirring device and heated to 50 °C in a water bath and stirred for 5 min;
[0052] ④Adjust stirring NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The speed of the O2 suspension device is such that it is stirred vigorously, and then the prepared buffer solution is poured into the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 suspension to obtain a mixed solution, to which ammonia water with a pH of 11 is added dropwise, the amount of ammonia water added is 3% of the volume of the mixed solution, so that the zirconium butoxide in the solution is hydrolyzed, and the solution is fully mixed, and then the speed is reduced and stirred for 30 minutes;
[0053] ⑤ The coated ZrO2@NaNi 1 / 3 Fe 1 / 3 Mn1 / 3 The O2 suspension is poured into a suction filtration device for filtration and washed 2 to 3 times;
[0054] ⑥ The filtered ZrO2@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 powder was placed in a vacuum oven for 6 h and then ground appropriately;
[0055] ⑦ Grind the ZrO2@NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was placed in an alumina crucible and calcined, starting from 20°C and heating up to 600°C at a rate of 5°C / min, and kept at 600°C for 4 hours, then cooled to room temperature and taken out.
[0056] Example 4 Material morphology and performance testing
[0057] 1. Sample characterization and testing
[0058] X-ray diffraction (XRD) technology is a commonly used test method for studying the phase and structure of crystals or the microstructure of some amorphous materials. In this experiment, the German Bruker D8 Advance intelligent X-ray diffractometer was used, with a radiation source of CuKα, a scanning range of 10~80°, and a scanning rate of 2° / min to test the crystal structure of the prepared NFM.
[0059] Scanning Electron Microscope (SEM) uses a highly focused electron beam to scan the surface of the sample being measured. The physical signals obtained are the interaction between the electron beam and the sample. The SEM equipment processes these physical signals to reflect the microscopic morphology of the material. The instrument used in this article is an ionizing double-beam electron microscope produced by TESCANBRNO in the Czech Republic to obtain sample surface information.
[0060] The XRD test results are as follows Figure 1 , Figure 2 and Figure 3 As shown, the spectrum has a flat background and sharp peaks, indicating that the material has a high degree of crystallinity. The positions of the remaining diffraction peaks completely correspond to the characteristic diffraction peaks of the standard card PDF#25-0819, indicating that the obtained material can be attributed to a layered O3 rhombohedral structure.
[0061] SEM test results are as follows Figure 4 , Figure 5 and Figure 6As shown, the samples are composed of flaky particles with an average size of about 2 μm, which are agglomerated by small particles with sufficient surface area, indicating that the three samples have good catalytic reaction activity for oxygen reduction with surface activity pointed out, and there is no obvious morphological difference in the shape and size of the sample particles after coating.
[0062] 2. Performance Testing Electrochemical Performance Testing
[0063] Hubei Lanbo BT-2018R multi-channel charge and discharge test system was used for constant current charge and discharge and cycle performance tests. Here, 1C is defined as 120 mA / g, and the charge and discharge voltage range is 2.0-4.0 V.
[0064] The discharge capacity curves of sodium ion batteries assembled by using ammonia to hydrolyze tetrabutyl titanate to prepare TiO2@NFM (Example 1) and using the same volume of deionized water to hydrolyze tetrabutyl titanate to prepare TiO2@NFM positive electrode material (the method is the same as Example 1, except that the ammonia in step ④ is replaced by the same volume of deionized water) are compared under 25°C, 1C conditions for 50 cycles. The results are as follows Figure 7 As shown, the TiO2@NFM positive electrode material prepared by hydrolyzing tetrabutyl titanate with deionized water has a capacity retention rate of only 75% after 50 cycles, while the TiO2@NFM positive electrode material prepared by hydrolyzing tetrabutyl titanate with ammonia water has a better reversible specific capacity, and the capacity retention rate after 50 cycles is about 89%, indicating that the material has good cycle stability.
[0065] The discharge capacity curves of sodium ion batteries assembled with NFM coated and uncoated NFM positive electrode materials in Examples 1, 2, and 3 were cycled 50 times at 25°C and 1C. The results are as follows: Figure 8 As described above, the capacity retention rate of the uncoated NFM material after 50 cycles is only 75%. In Examples 1, 2, and 3, the coated NFM has a better cycle life than the uncoated NFM material, and the capacity retention rates after 50 cycles are approximately 90%, 88.5%, and 81%, respectively. The material has good rate capability and certain cycle stability, and the entire preparation process is simple, and the raw materials are cheap and readily available.
[0066] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for wet coating sodium ion layered oxide positive electrode material, characterized in that: The following steps are involved: S1. The layered oxide cathode material of the sodium ion battery is dispersed in a dispersant, and then a buffer solution containing a metal organic salt is added under heating and stirring to obtain a mixed solution; S2. Add a certain amount of aqueous ammonia dropwise to the mixed solution, continue stirring, and perform hydrolysis and coating; S3. After coating, filter, wash, dry, grind and calcine to obtain the product.
2. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S1, the sodium ion battery layered oxide positive electrode material is selected from NaNi x Fe y Mn 1-x-y O2, wherein 0.2≤x≤0.5; 0.1≤y≤0.4; the dispersant is selected from anhydrous ethanol.
3. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S1, the metal organic salt is selected from aluminum isopropoxide, zirconium butoxide or tetrabutyl titanate; and the buffer solution is prepared by dissolving the metal organic salt in anhydrous ethanol to form a buffer solution.
4. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S1, the mass ratio of the sodium ion battery layered oxide positive electrode material to the metal organic salt is 1: (0.03-0.4); in the buffer solution, the concentration range of the metal organic salt solution is 1 mmol L -1 ~ 5mmol L -1 .
5. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S2, the pH range of the ammonia water is 10-12, and the amount of ammonia water added is 1%-5% of the volume of the mixed solution.
6. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S2, the hydrolysis and coating time is 20 to 30 minutes.
7. The method for wet coating of sodium ion layered oxide positive electrode material according to claim 1, characterized in that: In step S3, the drying time is 5-7 hours; the calcination temperature is 600°C-700°C.
8. A sodium ion layered oxide positive electrode material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 7.
9. Use of the sodium ion layered oxide positive electrode material according to claim 8 in the preparation of a sodium ion battery.
Citation Information
Patent Citations
Preparation method of oxide-coated double-element co-doped high-nickel ternary positive electrode material
CN114122349A
Coated modified sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117525338A